A STRATEGIC NEEDS-BASED COMMUNITY HEALTH ADMINISTRATION MODEL FOR SOCIAL DEVELOPMENT AND ADMINISTRATIVE REFORM: A CASE STUDY OF AN URBAN MUNICIPALITY IN THE PHILIPPINES - Salazar, Gina S (PEOPLE: International Journal of Social Sciences, 2016)
Despite the 4.02 social development rating of the Municipality of Hagonoy, its morbidity rate remains a core challenge; crude death rate is the lowest acceptable. These are symptomatic of governance failure in community health administration. This paper aims to create the Strategic Needs-based Community Health Administration (STRANCH-A) Model for the Municipality to address issues of adaptive mechanisms as interventions for emergent key health concerns, and of the vertical hierarchy in social development planning that results in the low ‘Fair’ Development Index for 2012. Participants include the present Municipal Council, Health Officer, Head of the Department of Social Welfare and Development, Planning and Development Officer, and Barangay Captains of the urban Municipality of Hagonoy, Bulacan. With Grounded Theory as approach, the author conducted a focus group discussion, a survey, and interviews; identified and categorized emergent key health concerns and existing interventions for them; and analyzed the relationship between these concerns and interventions. She examined the categories to discover new empowering interventions for sustainability for the creation of the STRANCH-A Model for Social Development meant to concretize and improve the process of planning and implementation in the area of community health. The analysis yielded four categorizations for levels of participant awareness on five sub-categorized emerging key health concerns. It was discovered that there existed a vertical hierarchy in administration of social development and that the women sector was affected by recurring gender-specific diseases. The STRANCH-A Model systematized the process of the administration of community health as a form of social development in the Municipality.